Taking Stock of Antidumping, Safeguards and Countervailing Duties, 1990-2009 - Bown, Chad P. (World economy, 2011)
This article examines the evolving, cross‐country use of antidumping, safeguard and countervailing duty policies – temporary trade barriers (TTBs) – over the period 1990–2009. I construct two new measures of imported products subject to the combined use of these TTBs before applying these measures to new data drawn from the World Bank’s Temporary Trade Barriers Database. I then establish a number of facts regarding trends in historical use to benchmark against policy activity during the global economic crisis of 2008–09. The 2008–09 economic shock mostly accentuates patterns and trends already visible in the precrisis data: e.g., while the major users of such policies overall combined to increase the product lines subject to TTBs by 25 per cent during the crisis, this was driven almost entirely by developing economies which increased their product coverage by 40 per cent. Perhaps surprisingly, recession‐affected high‐income economies increased their stock of product coverage by only 5 per cent during the crisis, a muted policy response consistent with earlier trends in which major developed economies like the United States and EU reduced the stock of imported products they subject to TTBs to 2007 levels that were only 50 per cent as high as their within‐period peak. Furthermore, a previously unidentified feature of the data is that a much larger share of China’s exported products to other developing economies is subject to foreign‐imposed antidumping than its exports to developed economies. The evidence confirms this feature is shared by a number of other major developing economy exporters, deepening concern that these discriminatory trade barriers are increasingly a ‘South–South’ phenomenon. Finally, I also clarify emerging trends in countervailing duty (anti‐subsidy) use across countries.